The fit between business model innovation and demand-side dynamics: catch-up of China's latecomer mobile handset manufacturers. Issue 2 (3rd April 2017) - Zhu, Hengyuan; Zhang, Marina Yue; Lin, Wenchen
Abstract: This paper aims to answer an important question: whether and how, in emerging markets, latecomer firms with limited technological endowments can catch up with industry incumbents that dominate the technological and market frontiers. Adopting the perspective of demand-side dynamics and analyzing the case of China's mobile handset manufacturing industry between 1998 and 2008, the paper finds that in emerging markets, latecomer firms with limited technological innovation capability are able to achieve market share catch-up by using effectiveness-centered business model innovation. Specifically, business model innovations that provided the most effective (though not necessarily the most efficient or novel) solutions to cater to changing customer preferences were the winners in helping latecomers achieve catch-up.